Subjective happiness and hope - Sariҫam, Hakan; Dumlupinar Universty (2015)
The aim of this research is to examine the relationships between subjective happiness and hope. The participants were 435 university students. In this study, the Integrative Hope Scale and the Subjective Happiness Scale were used. The relationships between were examined using correlation analysis and Structural Equation Model (SEM). In correlation analysis, trust and confidence, positive future orientation, and social relations and personal value sub factors of hope were found positively related to subjective happiness. On the other hand, lack of perspective sub factor of hope was found negatively correlated to subjective happiness. Structural Equation Model showed that subjective happiness was predicted positively by trust and confidence, positive future orientation, and social relations and personal value. However, subjective happiness was negatively explained by lack of perspective. According to standardized beta coefficients (β= 0.34), the most significant predictor of subjective happiness was trust and confidence. Results were discussed in the light of the related literature.